Vulnerability of social communication students. A case study - Ruiz Echeverry, Piedad (2019)
This article start with a research completed in 2018, whose goal was to identify situations and causes of physical, emotional, social and economic vulnerability of the students of the Social Communication´s program. In pursuit of this aim, four discussion groups, 125 surveys shaped with 49 closed questions each, provided the information for the analysis. The results of the research, enabled the identification of some socioeconomic characteristics of the students, such as that the program average student lives in low-middle class neighborhoods, does not get to have three proper meals a day and depends on his family to pay their student fees and their sustenance. The research also showed that belonging to the LGBTIQ+ population, parenting, and financial difficulties, represent some bigger student vulnerability conditions which impact in the quality of the training environment and the forming process itself.